Secretion of a mammalian chondroitinase ABC aids glial integration at PNS/CNS boundaries - Warren, Philippa M; Andrews, Melissa R; Smith, Marc; Bartus, Katalin; Bradbury, Elizabeth J; Verhaagen, Joost; Fawcett, James W; Kwok, Jessica C F (Scientific reports, 2020)
Schwann cell grafts support axonal growth following spinal cord injury, but a boundary forms between the implanted cells and host astrocytes. Axons are reluctant to exit the graft tissue in large part due to the surrounding inhibitory environment containing chondroitin sulphate proteoglycans (CSPGs). We use a lentiviral chondroitinase ABC, capable of being secreted from mammalian cells (mChABC), to examine the repercussions of CSPG digestion upon Schwann cell behaviour in vitro. We show that mChABC transduced Schwann cells robustly secrete substantial quantities of the enzyme causing large-scale CSPG digestion, facilitating the migration and adhesion of Schwann cells on inhibitory aggrecan and astrocytic substrates. Importantly, we show that secretion of the engineered enzyme can aid the intermingling of cells at the Schwann cell-astrocyte boundary, enabling growth of neurites over the putative graft/host interface. These data were echoed in vivo. This study demonstrates the profound effect of the enzyme on cellular motility, growth and migration. This provides a cellular mechanism for mChABC induced functional and behavioural recovery shown in in vivo studies. Importantly, we provide in vitro evidence that mChABC gene therapy is equally or more effective at producing these effects as a one-time application of commercially available ChABC.
Keywords: poranění míchy; Animals; pohyb buněk; neurity; chondroitinasa ABC; Neurites; centrální nervový systém; Axons; Genetic Therapy; Chondroitin Sulfate Proteoglycans; potkani Sprague-Dawley; zvířata; Central Nervous System; Lentivirus; neuroglie; Nerve Regeneration; Spinal Cord Injuries; Cell Adhesion; Rats, Sprague-Dawley; Integrins; Schwannovy buňky; genetická terapie; Chondroitin ABC Lyase; Neuroglia; Female; regenerace nervu; Rats; Cells, Cultured; Schwann Cells; astrocyty; neurony; axony; chondroitinsulfát proteoglykany; Peripheral Nervous System; integriny; Neurons; buněčná adheze; periferní nervový systém; krysa rodu Rattus; kultivované buňky; ženské pohlaví; Cell Movement; Astrocytes